2004
DOI: 10.1016/j.ehj.2003.12.017
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein elevation and disease activity in patients with coronary artery disease

Abstract: CRP levels predict future cardiovascular events independently of CAD severity and correlate with number of angiographically complex coronary artery stenosis in patients with ACS. Thus, CRP levels are a marker of atheromatous plaque vulnerability and CAD activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
73
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(87 citation statements)
references
References 31 publications
9
73
0
5
Order By: Relevance
“…Even in the absence of myocardial necrosis, however, the mere presence of an unstable plaque may be associated with higher circulating levels of inflammatory markers [14]. A ruptured plaque may be the responsible for the release of inflammatory cytokines to the coronary system [15].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of myocardial necrosis, however, the mere presence of an unstable plaque may be associated with higher circulating levels of inflammatory markers [14]. A ruptured plaque may be the responsible for the release of inflammatory cytokines to the coronary system [15].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, an elevated hsCRP might represent a more diffuse coronary atherosclerosis with a higher plaque burden. On the other hand, hsCRP was noted to correlate with the number of angiographically complex arterial stenoses and suggested to be a marker of plaque vulnerability and CAD activity [8]. However, no association of hsCRP with the number of stenotic vessels and the extent score was reported by Azar et al [14] in 98 patients, by Auer et al [15] in 100 patients, by Vesela et al [16] in 200 patients and by Hoffmeister at el.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated hsCRP levels have also been reported to be associated with an increased risk of further coronary events and rapid disease progression in patients with CAD [5,6,7]. It is suggested that hsCRP levels are a marker of CAD activity and atheromatous plaque vulnerability [8]. Plasma hsCRP can also be used to identify high-risk patients with CAD for appropriate therapies [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerotic burden, expressed in terms of number of coronary vessels involved by severe atherosclerosis [17], but also and more significantly in terms of number of ruptured plaques [18] seem to act as powerful stimuli for the inflammatory response represented by CRP release. Coronary plaque instability [19,20] or stenting due plaque instabilization have been reported as associated with increased CRP levels [21].…”
mentioning
confidence: 99%